2021
DOI: 10.1007/s11666-021-01242-7
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation Resistance of WC-10Co4Cr and WC-20CrC-7Ni HVAF Coatings

Abstract: Machines operating in aqueous environments may be subjected to cavitation damage during operation. This study aims to evaluate the cavitation resistance of WC-10Co4Cr and WC-20CrC-7Ni coatings under cavitation erosion conditions with additional electrochemical effects. The coatings were deposited on AISI 1040 steel substrates using a high velocity air fuel thermal spray process. The microstructure of the coatings was observed by a scanning electron microscope, while their phase composition was analyzed using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…It could provide qualitative images at the microscale level and further evaluate the degree of corrosion surface coverage. 32 The results of measurements are shown in Fig. 8 and 9 .…”
Section: Resultsmentioning
confidence: 98%
“…It could provide qualitative images at the microscale level and further evaluate the degree of corrosion surface coverage. 32 The results of measurements are shown in Fig. 8 and 9 .…”
Section: Resultsmentioning
confidence: 98%
“…Different surface engineering technologies, particularly coating processing options, such as electroplating and electroless technologies, thermal spray, microwave cladding, friction stir processing, plasma‐assisting technology, PVD, CVD, and some others can be basically considered and employed for steel protection by hard layers. Ceramic (oxide and non‐oxide) or composite protective layers (e.g., CMC, MMC, and DLC) have higher potential 124–136 . However, many of the listed options are not well suited for industrial applications in mining and mineral processing, either because they cannot withstand severe abrasive and erosive conditions required by the industry, or because they are not applicable for the inner surface protection of long tubing and complex shape components.…”
Section: Major Advanced Ceramic Composite or Coating Materials For Pr...mentioning
confidence: 99%
“…Varis et al [10] proposed that high compressive stresses of HVAF-coatings inhibit the fatigue crack formation and propagation along the microstructure consisting of lamellae interfaces, thus improving the cavitation resistance of the coating. According to Korobov et al [9], the fine structure of WC-CrC-Ni coating increases the specific surface area of carbide particles and, consequently, the required crack propagation energy.…”
Section: Hvaf Coatings Against Cavitation Erosionmentioning
confidence: 99%
“…In turn, this improves their resistance to chipping and consequently, to cavitation compared to the coarser WC-CoCr coating (Figure 7). In the case of the WC-CrC-Ni coating, the hardening of the matrix caused by the dissolution of Cr is accompanied by an increase in the matrix's plasticity, which prevents carbides from detaching from the matrix [9]. Kumar et al [18] reported that spraying parameters (e.g., particle velocity) affected the mechanical properties of HVAF-sprayed tungsten carbide coatings (e.g., fracture toughness), influencing the resultant cavitation resistance.…”
Section: Hvaf Coatings Against Cavitation Erosionmentioning
confidence: 99%
See 1 more Smart Citation